PTH-090 Laboratory experience of anti-tnf drug monitoring in routine practice – perspective from the first uk centre. (22nd June 2015) - Arkir, Z; Unsworth, N; Richards, G; Odho, Z; Irving, PM
Abstract : Introduction: Therapeutic drug monitoring (TDM) of Infliximab (IFX) and Adalimumab (ADAL) has been in use in our centre since 2012. Here we present the TDM experience of our laboratory service at Viapath, St Thomas' Hospital. Method: Anti-TNF requests received between June 2012 and January 2015 were reviewed. All assays were performed using LISA-TRACKER Duo kits automated on eRobot (Theradiag, France). These assays measure free drug and anti-drug antibody (ADAb) and therefore inhibition studies were performed on samples with detectable drug levels (>1 ug/ml) and positive ADAb. Results were classified according to drug levels (DL) and ADAb status. Results: The laboratory analysed 2424 (17% internal) samples for IFX (Median DL 3.8 ug/mL, IQR 1.2–6.3) and 1335 (21% internal) samples for ADAL (Median DL 5.2 ug/mL, IQR 3.4–7.3) from IBD patients. Prevalence of detectable antibodies was higher in IFX (10%) than ADAL (4.1%) samples. External requests originated from >90 different hospitals. Number of requests received for both assays doubled from 2013 to 2014 with batch frequency consequently decreasing from fortnightly to weekly. 40 patients had IFX >1 ug/ml and were antibody positive. 16 of these patients were confirmed to have switched to ADAL due to loss of response to IFX therapy. Detectable DL observed in these cases was due to cross reactivity of ADAL with the IFX assay. 11 patients had false positive drug levels and 4 patients had borderline antibodies due to non specific binding. 1 patient had sample collected around infusion. 4 patients had subtherapeutic ADAL (1.1–1.4 ug/ml) and were antibody positive. 1 of these patients was confirmed to have switched to IFX due to loss of response to ADAL therapy. Detectable DL observed in this case was due to cross reactivity of IFX with the ADAL assay. 3 patients had false positive results for ADAL. From the data, it was evident that some centres monitored patients with serial measurements and made subsequent changes to therapy. 63 patients (IFX) and 52 patients (ADAL) had an average of 7 and 3 repeat measurements taken respectively. Conclusion: Anti-TNF testing has been embedded in several IBD centres as a way of optimising therapy however variation in TDM practices was observed highlighting the need for national guidance. Significant increase in test requesting suggests assay based treatment strategies combined with clinical assessment is now an accepted practice in IBD. Disclosure of interest: Z. Arkir: None Declared, N. Unsworth: None Declared, G. Richards: None Declared, Z. Odho: None Declared, P. Irving Speaker Bureau of: MSD, Abbvie and Takeda.